MANAGING AIRCRAFT GROUND HANDLING DELAYS IN VIETNAM AIRLINES BY USING SUPPLY CHAIN STRATEGY - Hong Le, Doan; G. Aquino, Perfecto; Le Phuong, Nguyen (International Journal of Supply Chain Management, 2019)
Punctuality is one of the key performance indicators in the airline industry and an important service differentiator especially for valuable high-yield customers based on the supply chain strategy. In addition, improved on-time performance can help achieve significant cost savings. Airlines report delay costs from 0.6 to up to as much as 2.9% of their operating revenues. Vietnam Airlines (VNA) stated that they want to convey passengers or freight from one point to another with maximum safety, efficiency and on time performance. However, within 12.34% of delayed flights in 2011due to aircraft ground handling (annual reportâ??s TOC), VNA operation is not very effective in aircraft ground handling. The project is about aircraft ground handling process in VNA. Supply chain strategy can be used in airlines to improve its fluency.